A real-time acoustic signature-based fluid identification methodology for applications in the field of security and defence. (2016) - Singh, Shweta; Bansal, Dipali
Acoustic-based inspection methods, employed for on field screening of containers, hold high importance in the fields of security and defence. However, such methods are limited by expensive instrumentation, offline analysis and complexities related to transducer container physical coupling. Simple, non-destructive and extremely cost effective method based on acoustic resonance has been devised here for rapid online acquisition and analysis of acoustic signatures of fluids for their necessary identification and classification. The research, with two stages of experimentation, establishes reliability of the system in the first stage by using sweep excitation in fluids followed by acquiring acoustic signatures for such fluids in the second stage by using white noise for excitation. The setup uses two ceramic coated piezoelectric transducers interfaced with the computer through audio ports. Excellent consistency in the results, recorded with the help of a virtual spectrum analyzer, is achieved with average error amounting to 1.4%.